IMPLEMENTASI KEBIJAKAN E-GOVERNMENT PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN NGANJUK - Rubiyanto Rubiyanto (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
E-Government program is a form of the implementation of public services based information technology and communication that covertly designed to make the process of working in the government of into simpler ones, more accurate, responsive and transparent. With the establishment of presidential instruction no 3 2003, instructed that all government agencies apply for the e-Government program. BAPPEDA has implemented through a system of e-Government program information regional development planning or e-Planning. This study determines to reveal an understanding of the e-Government of policy on Regional Development Planning Board District Nganjuk. Technique data analysis using a technique qualitative according to data analysis Miles and Huberman. The research results show that of policy e-Government on Regional Development Planning Board District Nganjuk has been implemented by an instruction of the president number three years 2003; however, in practice, there are several problems can slow process implementation e-Government itself.